2019
DOI: 10.4310/jsg.2019.v17.n6.a7
|View full text |Cite
|
Sign up to set email alerts
|

Symplectic divisorial capping in dimension $4$

Abstract: We investigate the notion of symplectic divisorial compactification for symplectic 4-manifolds with either convex or concave type boundary. This is motivated by the notion of compactifying divisors for open algebraic surfaces. We give a sufficient and necessary criterion, which is simple and also works in higher dimensions, to determine whether an arbitrarily small concave/convex neighborhood exist for an ω-orthogonal symplectic divisor (a symplectic plumbing). If deformation of symplectic form is allowed, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 51 publications
(148 reference statements)
0
31
0
Order By: Relevance
“…which is the proper transform of a complex line and a smooth conic in general position in CP 2 , obtained by blowing up at 4 + n generic points of the conic and one generic point of the complex line, such that the boundary of a closed regular neighborhood of D is −M n . Since the intersection matrix of D is nonsingular and not negative definite, by[LM, Theorem 1.3] (see also…”
mentioning
confidence: 99%
“…which is the proper transform of a complex line and a smooth conic in general position in CP 2 , obtained by blowing up at 4 + n generic points of the conic and one generic point of the complex line, such that the boundary of a closed regular neighborhood of D is −M n . Since the intersection matrix of D is nonsingular and not negative definite, by[LM, Theorem 1.3] (see also…”
mentioning
confidence: 99%
“…Here is a local criterion. The first statement is observed in [12]. Moreover, tori blow-up/down is a local operation that does not change the the diffeomorphism type of Y D and the exactness of ω| Y D .…”
Section: Contact Aspectsmentioning
confidence: 92%
“…Therefore by [17] the plumbing P A supports a symplectic structure where the core spheres of the plumbing are symplectic, they intersect ω-orthogonally, and there is an inward pointing Liouville vector field demonstrating that the boundary is concave.…”
Section: Non-fillable Contact Manifoldsmentioning
confidence: 98%
“…Explicit constructions of symplectic structures on plumbings were first studied by Gay and Stipsicz in [7] to produce symplectic negative definite plumbings with convex boundary. This construction was extended by Li and Mak to the concave case in [17], where it is shown that a plumbing supports a symplectic structure with concave boundary if the plumbing graph satisfies the positive G-S criterion. This means that if Q is the pk`N qˆpk`N q intersection matrix for the plumbing, there exists z P p0, 8q k`N such that Qz is a vector with all positive components.…”
Section: Non-fillable Contact Manifoldsmentioning
confidence: 99%